Addressing cultural diversity in preparing teachers for openness: culturally sensitive appropriation of open content - Malgorzata Kurek (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Open educational content and its accessibility is a frequently discussed theme, yet it is only recently that attention has been given to the processes of cross-cultural reusing and adapting Open Educational Resources (OER). This study builds on the idea that since its potential for adaptability is an inherent feature of open content, the quality of instructional design should be seen as the relation between the original version and its locally appropriated adaptation (Conole & Ehlers, 2010; King, 2013). This goes hand in hand with the current trends to link quality in education with its relevance to learners' individual needs (Tikly & Barrett, 2011). For these reasons, we argue that due attention should be given to the processes of pedagogical adaptation and localisation so that resources and practices become culturally valid to the target users and respond to their unique educational cultures. In the study we investigate the strategies employed by colleagues representing six different national contexts in the process of cultural adaptation of a set of teacher-development instructional materials. The analysis shows that efficient re-use and adaptation of open content require providers to be sensitive to characteristics of target educational contexts and tailor the materials accordingly.